Effects of high doses of inhaled corticosteroids on adrenal function in children with severe persistent asthma. - Ninan, T K (1993)
BACKGROUND--Childhood asthma generally responds well to inhaled corticosteroids within the dosage range recommended by the manufacturers, but it is sometimes necessary to use higher doses--that is, above 400 micrograms/day--a practice which has become more widespread recently. Whereas the lack of adrenal suppression in children given inhaled corticosteroids in normal doses is well documented, little is known about the effects of higher doses. METHODS--The effects on adrenal function of high dose (above 400 micrograms/day) inhaled corticosteroids were evaluated by measuring cortisol concentration in the morning and performing a short tetracosactrin test in 49 children taking budesonide (mean age 9.2 years (range 4 to 16 years) and 28 children taking beclomethasone dipropionate (10.2 years (5 to 13 years)). Twenty three non-asthmatic children (8.9 years (4.9 to 13 years)) who were under investigation for short stature served as controls for the study. RESULTS--Compared with controls mean basal cortisol concentration was lower in children taking budesonide and beclomethasone dipropionate (control 401 (26.8) nmol/l, budesonide 284 (22) nmol/l, beclomethasone dipropionate 279 (23.2) nmol/l). Sixteen of the 49 children taking budesonide had subnormal basal cortisol concentrations compared with seven of the 28 taking beclomethasone dipropionate. Mean stimulated cortisol concentrations were lower in children taking inhaled corticosteroids than in controls, with no difference between those taking budesonide or beclomethasone dipropionate. CONCLUSIONS--Adrenal suppression occurs in some children who are given inhaled corticosteroids in doses greater than 400 micrograms/day. It may therefore be advisable to try alternative treatments before such doses are used.